The effect of carbonyl defect on the electrode injection characteristics of polytetrafluoroethylene film capacitor. (July 2022) - Duan, Wei; Guo, Guangzhi; Pu, Lu; Wu, Jian; Sun, Haofei; Zhao, Xuefeng; Deng, Junbo
Abstract: Polymer dielectric capacitor for high energy storage is a promising energy storage technology. However, in dielectric capacitor electrode injection process may occur at the metal plate/organic polymer interface under high applied electric field, and the injected carriers will lead to the distorted electric field and the accumulation of space charge in dielectric material, which can seriously cause the breakdown of the capacitor. Furthermore, chemical defects in polymer dielectric may aggravate this effect of electrode injection. For this, based on the first principle simulation method, the effect of carbonyl defect on electrode injection properties at aluminum/polytetrafluoroethylene (PTFE) interface are studied to reveal the harm of chemical defect to dielectric capacitor insulation and to explain the potential physical mechanism. The results showed that the carbonyl defect can increase the vacuum level shift of interface and electron affinity of PTFE molecule, while decrease the ionization potential of PTFE molecule, which significantly reduce the interface charge injection barrier. Compared with the ideal interface, the electron injection barrier at the carbonyl defect interface decreased from 3.40eV to 2.29eV, and the hole injection barrier decreased from 7.39eV to 5.80eV. As a result, the injection current density of the interface with carbonyl defect is significantly higher under the same electric field.